?THE DISTRIBUTION OF Mn, Zn, Cu, Cr, Ni, AND Pb AROUND TWO MAJOR REFUSE DUMPSITES IN BENIN CITY, NIGERIA (Biological Sciences - PJSIR, 2003)
The concentration of Zn, Pb, Mn, Cu, Cr and Ni around two major refuse dumpsites in Benin City have been determined. This was done in order to ascertain the suitability of these area of land for residential and agricultural purposes when eventually reclaimed. In all, 18 soil samples were collected at distances of 0 m, 50 m and 100 m (9 top soil; 0 to 15 cm and 9 bottom soil; 15 to 30 cm) from each dumpsite. Sample solutions were prepared and analysed using atomic absorption sepectrophotometry. Results obtained indicate that top-soil samples from Ugbowo dumpsite contain as much as 1.10 - 8.88 mg/kg Mn, 0.68 - 2.30 mg/kg Zn, 5.90 - 8.70 mg/kg Cu, 0.08 - 0.16 mg/kg Cr, 0.50 - 77 mg/kg Ni and 0.10 - 0.45 mg/ kg Pb. Bottom soil samples from the same dumpsite gave ranges of 4.44 - 15.26 mg/kg Mn, 0.84 - 6.59 mg/kg Zn, 5.30 - 7.70 mg/kg Cu, 0.11 - 0.20 mg/kg Cr, 0.66 - 1.57 mg/kg Ni and 0.20 - 0.60 mg/kg Pb. For Evbuotubu dumpsite, concentration ranges obtained for the top soil samples are 5.72 - 18.33 mg/kg of Mn, 2.10 - 5.23 mg/kg of Zn, 1.96 - 12.22 mg/kg of Cu, 0.22 - 0.56 mg/kg of Cr, 0.27 - 0.83 mg/kg of Ni and 0.72 - 1.20 mg/kg of Pb. Bottom soil samples gave concentration ranges of 3.24 - 17.96 mg/kg of Mn, 1.46 - 6.20 mg/kg of Zn, 4.33 - 10.93 mg/kg of Ni and 0.69 - 1.51 mg/kg Pb. The heavy metal levels were found to decrease in both top and bottom soils with distance from the dumpsites.